Pengaruh Promosi Media Sosial Dan Kualitas Pelayanan Terhadap Minat Berkunjung Kembali Di Wisata Alas Hills Kota Cane, Kecamatan Babussalam Kabupaten Aceh Tenggara - Hera Br Togatorop; Irwansyah Putra; Nindya Yunita (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to find out the influence of social media promotion and service quality on the interest of returning to Alas Hills Tourism in Cane City, Babussalam District, Southeast Aceh Regency. The phenomenon behind this research is that there is still low access to tourist information through social media and the quality of service that is considered not optimal, such as irregularity of parking areas, lack of entrance fees, lack of identity of officers, and services that are not yet responsive. This research uses a quantitative approach with the type of explanatory research. The study population consisted of 16,270 visitors, and the sample was determined using the Slovin formula so that 99 respondents were selected through the purposive sampling technique. Data collection is done through the distribution of questionnaires, interviews, and documentation studies. Data is processed using SPSS 27 analysis tool Data analysis technique using multiple linear regression analysis, t test, F test, and coefficient of determination (R²). The research results show that: (1) Social media promotion has a positive and significant effect on the interest of returning, which means that the better the promotion is carried out through digital platforms, the higher the interest of tourists to visit again. (2) The quality of service has a positive and significant effect on the interest in returning, showing that good service is able to create a positive experience for visitors. (3) Social media promotion and service quality simultaneously have a positive and significant effect on the interest in returning. Thus, tourism managers are expected to improve digital promotion strategies and improve service quality to increase visitor loyalty.